2020
DOI: 10.1007/s00330-020-06669-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for the outcome of needle aspiration of calcific deposits for rotator cuff calcific tendinitis

Abstract: Objective To identify prognostic factors for the effectiveness of needle aspiration of calcific deposits (NACD) for rotator cuff calcific tendinitis (RCCT) Methods One hundred forty-nine patients with symptomatic RCCT were included in a prospective cohort study. Pain (VAS), shoulder function (SST and DASH), and quality of life (EQ-5D) were assessed at baseline and at 3, 6, and 12 months post-NACD. Univariate analyses (independent t tests or Mann-Whitney U tests depending on the distribution of data) were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 24 publications
(40 reference statements)
3
24
0
Order By: Relevance
“…Some authors have reported an increased chance of spontaneous disappearance for type III calcifications. 5,16,27 de Witte et al 12 also found a better outcome for patients undergoing UGPL with type II and III calcifications versus type I. Oudelaar et al 28 found that smaller-sized calcifications had a worse prognosis. We failed to demonstrate the same association using a cutoff of 10 mm to define small calcifications, but we confirmed a weak but significant negative correlation between size and DASH score at 6 months (r = 20.259, P = .003; data not shown).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Some authors have reported an increased chance of spontaneous disappearance for type III calcifications. 5,16,27 de Witte et al 12 also found a better outcome for patients undergoing UGPL with type II and III calcifications versus type I. Oudelaar et al 28 found that smaller-sized calcifications had a worse prognosis. We failed to demonstrate the same association using a cutoff of 10 mm to define small calcifications, but we confirmed a weak but significant negative correlation between size and DASH score at 6 months (r = 20.259, P = .003; data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…Aina et al 1 were the first to describe a relationship between calcium aspiration and the success of the procedure. Some authors, however, were not able to confirm this association, including del Cura et al 11 and Oudelaar et al 28 Moreover, the success of simply fragmenting the calcific deposits without aspiration raised the question of whether it was necessary to perform a lavage of the calcific deposit during the procedure. 19,34 Importantly, we showed that the quantity of calcium extracted was not significantly associated with the outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, rates of up to 45% have been published. 35 A possible explanation might be that patients with Gartner and Heyer type 3 calcifications were excluded from participation in this study. It is known that patients with Gartner and Heyer type 1 calcific deposits are more likely to need multiple NACD procedures compared with patients with type 3 calcific deposits.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that patients with Gartner and Heyer type 1 calcific deposits are more likely to need multiple NACD procedures compared with patients with type 3 calcific deposits. 35 Furthermore, patients were monitored more closely during the study, which could be a possible other explanation for the relatively high rate of secondary procedures.…”
Section: Discussionmentioning
confidence: 99%